Administrative management in agricultural grain conservation processes in Sinaloa, Mexico - Alfonso Reyna Parra (Technium Social Sciences Journal, 2025)
The aim of this paper is to analyse the conditions of administrative management in agricultural grain preservation processes in Sinaloa, considering that the storage procedures of these products represent an important part of the work of this sector. Storage and conservation require a necessarily careful administrative organisation, which also incorporates important safety processes due to the risks and the maintenance of the product in healthy conditions. In the case of maize, companies in the region have an important relationship with storage in conservation silos, where there is a link with regional economic conditions and work culture. Hypothesis: The use of storage technologies requires extraordinary management and organisational processes because of the risks involved. The entrepreneur in the region leads the administrative organisation to regular levels, without applying the greatest effort considering cost reduction, so that the individual interest is emphasised in relation to employment and wages.